1984
DOI: 10.1002/j.1460-2075.1984.tb01982.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the clustered mitochondrial tRNA genes in Saccharomyces cerevisiae: transcription and processing of transcripts.

Abstract: The transcripts of a cluster of eight tRNA genes localized in the Cap-oxiI region of the mitochondrial genome of Saccharomyces cerevisiae were investigated by hybridization of gene-specific probes on Northern blots of mitochondrial RNA and by SI mapping of the 5' termini of the transcripts. Two rho-mutants that lack mature tRNA species and accumulate precursors have been used to detect transcripts that are not detectable in wild-type (w.t.) mitochondria. The results have shown the existence of polygenic transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…The existence of high-molecular-mass transcripts hybridizing with tRNA gene probes had previously been observed [27]. The steady-state levels of such transcripts did not increase appreciably in derepressed cells, while the levels of many medium-sized transcripts exhibited strong variations in the two conditions.…”
Section: Release From Glucose Repression In Resting Cellsmentioning
confidence: 73%
See 1 more Smart Citation
“…The existence of high-molecular-mass transcripts hybridizing with tRNA gene probes had previously been observed [27]. The steady-state levels of such transcripts did not increase appreciably in derepressed cells, while the levels of many medium-sized transcripts exhibited strong variations in the two conditions.…”
Section: Release From Glucose Repression In Resting Cellsmentioning
confidence: 73%
“…4d) were also detected (after prolonged exposure) with probes from the cotranscribed varl and olil genes (not shown) [26]. We had previously demonstrated that processing of polygenic tRNA precursors occurs in wild-type cells at the 5' and 3' ends of tRNA sequences and at some G+C-rich clusters localized in the long intergenic regions [27]. As a possible approach to identifying the basis of differences observed in the processing pathways of tRNA precursors, under different conditions, we examined, in S1 mapping experiments, the 5' ends of the tRNA-sequence-containing transcripts present in repressed and derepressed cells.…”
Section: Release From Glucose Repression In Resting Cellsmentioning
confidence: 78%
“…The presence of RNase P activity in vitro directly correlated with the presence of a locus on yeast mitochondrial DNA previously shown by genetic and biochemical studies to be required for tRNA maturation. The product of the locus, the 9S RNA, and this newly described mitochondrial RNase P activity cofractionated, providing further evidence that the 9S RNA is the RNA component of yeast mitochondrial RNase P. tRNA genes in yeast mitochondria are transcribed into large RNA precursors, either alone or contiguous with mRNA, rRNA, or additional tRNA transcripts (14,16,20,24). Maturation steps include endonucleolytic cleavage of 5' leading and 3' trailing sequences, addition of CCA at the 3' terminus, and modification of some of the bases.…”
mentioning
confidence: 77%
“…Transcript mapping shows that other 5' tRNA leaders result from cleavage events that separate precursors * Corresponding author. from polycistronic RNA molecules (6,20,24). tRNA precursors of both origins require the tRNA synthesis locus for 5' leader processing (23).…”
mentioning
confidence: 99%
“…The PstI palindromes in N. crassa mtDNA may be analogous to the GC-rich HpaII + HaeIII clusters of S. cerevisiae mtDNA, which are also conserved (although several different families have been described), are found mostly in intergenic spacers, and frequently contain inverted repeats (Prunell and Bernardi, 1977). Although the GC clusters of S. cerevisiae mitochondria have been postulated to be involved in RNA processing, there is only one documented case in which processing of a transcript containing several tRNA genes occurs within a GC cluster (Palleschi et al, 1984). Several cases of optional GC clusters near or within S. cerevisiae mitochondrial genes are known, and there is even an optional GC cluster within the reading frame of the varl ribosomal protein gene (Hudspeth et al, 1984;Dujon, 1980;Sor and Fukuhara, 1982).…”
Section: Discussionmentioning
confidence: 99%